Local formation of HArF in solid argon: Low-temperature limit and thermal activation - Lignell*, H.; Khriachtchev, L.; Lignell**, A.; Räsänen, M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
The H + Ar + F reaction leading to HArF formation in an argon matrix is studied at temperatures down to8 K. The effects of the precursor concentration, deuteration, IR light, and deposition temperature as well asthermal activation of this reaction are studied. It is found that HArF molecules are formed slowly but efficientlyat 8 K in a photolyzed HF/Ar matrix, supporting the previously reported results. The formation rate of HArF(and DArF) exhibits a low-temperature limit and enhances at elevated temperatures with activation energy of ca. 40 meV. All the data show that HArF is formed as a result of a local reaction of hydrogen atoms with the parent Ar−F centers and the tunneling mechanism is very probable here. The locality of the precursor photolysis required for this tunneling reaction is consistent with the partial HArF formation observed during photolysis of HF in an argon matrix. The decay mechanism of (ArHAr)+ cations is also studied. The present results confirm the previous conclusions that the decay of the cations is not essentially connected to the HArF formation.